Resin composition and product thereof
By using resin compositions containing vinyl polyphenylene ether resin, divinylbenzene-styrene-ethylene ternary polymer and specific compounds, the shortcomings of existing materials in the copper foil substrate are solved and the copper foil stripping is improved The strength, water absorption rate and dielectric loss meet the comprehensive needs of high-performance substrates.
Patent Information
- Application Number
- CN202310860741.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-07
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-10
AI Technical Summary
Existing materials cannot meet the comprehensive performance requirements of copper foil substrates for highly functional, miniaturized and multilayered circuit boards, especially in terms of copper foil peel strength, water absorption rate and dielectric loss.
Provided is a resin composition comprising 100 parts by weight of a vinyl polyphenylene ether resin, 20 parts by weight to 60 parts by weight of divinylbenzene-styrene-ethylene ternary polymer and 5 parts by weight to 15 parts by weight of Compounds with specific structures are used to make semi-cured sheets, resin films or laminated plates to enhance the performance of copper foil substrates.
It achieves excellent copper foil peel strength, water absorption rate and dielectric loss performance on copper-containing substrates, meeting the comprehensive needs of high-performance substrates.
Smart Images

Figure CN119286229A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and products thereof. Background Art
[0002] The operation of electronic equipment is achieved by connecting numerous electronic components through conductive lines on a circuit board for power supply and signal transmission. A circuit board is generally composed of a circuit substrate and a conductive line pattern located on the circuit substrate.
[0003] With the rapid development of the fifth generation mobile communication technology (5G) and the high functionality and miniaturization of electronic devices, the circuit boards used are also moving towards multi-layering, high wiring density and high-speed signal transmission. Correspondingly, in order to ensure the quality of electronic devices, higher requirements are placed on the comprehensive performance of circuit substrates (such as copper foil substrates).
[0004] Therefore, how to develop a material suitable for high-performance substrates is the direction that the industry is currently actively working towards. Summary of the invention
[0005] In view of the problems encountered in the prior art, especially the inability of existing materials to meet one or more of the above performance requirements, the main purpose of the present invention is to provide a resin composition and its products that can meet the above performance requirements.
[0006] The present invention provides a resin composition, comprising:
[0007] 100 parts by weight of a vinyl-containing polyphenylene ether resin;
[0008] 20 to 60 parts by weight of a divinylbenzene-styrene-ethylene terpolymer; and
[0009] 5 to 15 parts by weight of a compound having the structure of formula (1),
[0010]
[0011] Wherein, R1, R2, R3, and R4 each independently represent an alkylene group having 1 to 4 carbon atoms or hydrogen.
[0012] One embodiment of the present invention provides an article made of the resin composition, wherein the article includes a prepreg, a resin film, a laminate or a printed circuit board.
[0013] Articles made from the resin composition of the present invention, such as prepregs, resin films, laminates or printed circuit boards, have excellent properties in at least one of copper foil peel strength, water absorption and dielectric loss of copper-containing substrates, and can therefore become high-performance substrates that meet comprehensive requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Schematic diagram of the substrate appearance dry plate.
[0015] Figure 2 This is a schematic diagram of a normal substrate appearance.
[0016] Figure 3 Schematic diagram of the substrate having dendritic stripes on the surface.
[0017] Figure 4 Schematic diagram of the substrate appearance without dendritic stripes. DETAILED DESCRIPTION
[0018] The detailed features and advantages of the present invention are described in detail in the following embodiments, and the contents are sufficient to enable any person skilled in the art to understand the technical content of the present invention and implement it accordingly, and according to the contents disclosed in this specification, the claims and the drawings, any person skilled in the art can easily understand the relevant purposes and advantages of the present invention. The following examples further illustrate the viewpoints of the present invention in detail, but do not limit the scope of the present invention in any viewpoint.
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.
[0020] As used herein, the terms "comprises," "including," "having," "containing," or any other similar terms are open-ended transitional phrases that are intended to cover non-exclusive inclusions. For example, a composition or article containing a plurality of elements is not limited to those elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless expressly stated to the contrary, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as specifically disclosing and simultaneously covering closed conjunctions such as "consisting of", "consisting of", and "the remainder is", as well as conjunctions such as "substantially consisting of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".
[0021] As used herein, the phrase “a composition comprises A, B and C, wherein A comprises a1, a2 or a3.” has the same meaning as “a composition comprises A, B and C, wherein A comprises a1, a2, a3 or a combination thereof.”, that is, “a composition comprises A, B and C, wherein A comprises a1, a2, a3, a combination of a1 and a2, a combination of a1 and a3, a combination of a2 and a3, or a combination of a1, a2 and a3.”.
[0022] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents and concentrations, are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual numerical values within the range (including integers and fractions), especially integer numerical values. For example, the range description of "1.0 to 8.0", "1.0-8.0", "between 1.0 and 8.0" or "between 1.0 and 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, and includes endpoint values, especially sub-ranges defined by integer numerical values, and should be deemed to have specifically disclosed individual numerical values such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, etc.
[0023] In this document, numerical values should be understood to have the precision of the significant digits of the numerical value, provided that the purpose of the present invention can be achieved. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.
[0024] Unless otherwise specified, in this article, polymer refers to the product formed by the polymerization reaction of monomers, including aggregates of many macromolecules, each of which is composed of many simple structural units repeatedly connected by covalent bonds. Monomers are compounds that synthesize polymers. Polymers can include homopolymers (also known as self-polymers), copolymers, prepolymers, etc., and are not limited to them. Prepolymers refer to chemical substances produced by polymerization reactions of two or more compounds with a conversion rate between 10% and 90%. Polymers also include oligomers, and are not limited to them. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually polymers composed of 2 to 5 repeating units. For example, when interpreting diene polymers, they include diene homopolymers, diene copolymers, diene prepolymers, and of course diene oligomers, etc.
[0025] Unless otherwise specified, in this article, copolymer refers to a product formed by polymerization of two or more different monomers, including but not limited to a random copolymer (also known as a random copolymer), an alternating copolymer, a graft copolymer or a block copolymer. For example, a styrene-butadiene copolymer is a product formed by polymerization of only two monomers, styrene and butadiene. For example, a styrene-butadiene copolymer includes but is not limited to a styrene-butadiene random copolymer, a styrene-butadiene alternating copolymer, a styrene-butadiene graft copolymer or a styrene-butadiene block copolymer. A styrene-butadiene block copolymer includes, for example but not limited to, a molecular structure after polymerization of styrene-styrene-styrene-butadiene-butadiene-butadiene. A styrene-butadiene block copolymer includes, for example but not limited to, a styrene-butadiene-styrene block copolymer. A styrene-butadiene-styrene block copolymer includes, for example but not limited to, a molecular structure after polymerization of styrene-styrene-styrene-butadiene-butadiene-butadiene-styrene-styrene. Similarly, the hydrogenated styrene-butadiene copolymer includes a hydrogenated styrene-butadiene random copolymer, a hydrogenated styrene-butadiene alternating copolymer, a hydrogenated styrene-butadiene graft copolymer or a hydrogenated styrene-butadiene block copolymer. The hydrogenated styrene-butadiene block copolymer includes, for example but not limited to, a hydrogenated styrene-butadiene-styrene block copolymer.
[0026] If not otherwise specified, "resin" is generally a customary name for a synthetic polymer, but in this article, "resin" can include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, and is not limited thereto. For example, in this article, "maleimide resin" can include maleimide monomers, maleimide polymers, combinations of maleimide monomers, combinations of maleimide polymers, or combinations of maleimide monomers and maleimide polymers.
[0027] In this article, "containing a vinyl group" is interpreted to include a vinyl group, a vinylidene group, an allyl group, or a (meth)acrylate group, wherein the vinyl group includes a vinylbenzyl group.
[0028] If not otherwise specified, herein, modified products (also referred to as modified products) include: products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after homopolymerization of each resin, products after copolymerization of each resin with other resins, etc. For example, modification may be to replace the original terminal hydroxyl group with a terminal vinyl group through a chemical reaction, or to obtain a terminal hydroxyl group by chemically reacting the original terminal vinyl group with p-aminophenol (also referred to as p-aminophenol).
[0029] If not otherwise specified, the unsaturated bond described in the present invention refers to a reactive unsaturated bond, such as but not limited to an unsaturated double bond that can undergo a cross-linking reaction with other functional groups, such as but not limited to an unsaturated carbon-carbon double bond that can undergo a cross-linking reaction with other functional groups.
[0030] If not otherwise specified, in this article, when a specific example of a compound is written in the form of "(substituent)", it should be understood to include both the case where the substituent is included and the case where the substituent is not included. For example, cyclohexanedimethanol di(meth)acrylate should be understood to include cyclohexanedimethanol diacrylate and cyclohexanedimethanol dimethacrylate, and (meth)acrylate should be understood to include acrylate and methacrylate.
[0031] If not otherwise specified, the alkyl group described in the present invention includes its various isomers when interpreted. For example, propyl group should be interpreted as including n-propyl group and isopropyl group.
[0032] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present application, as long as there is no contradiction in the combination of these features.
[0033] Unless otherwise specified, parts by weight herein represent parts by weight, which may be any weight unit, such as but not limited to kilograms, grams, pounds, etc. For example, 100 parts by weight of maleimide resin may represent 100 kilograms of maleimide resin or 100 pounds of maleimide resin. If the resin solution includes a solvent and a resin, the parts by weight of the (solid or liquid) resin generally refers to the weight unit of the (solid or liquid) resin, and does not include the weight unit of the solvent in the solution, while the parts by weight of the solvent refers to the weight unit of the solvent.
[0034] The following detailed description is merely illustrative in nature and is not intended to limit the present invention and its uses. In addition, this article is not limited by any theory described in the above-mentioned prior art or summary of the invention or the following detailed description or examples. The methods, reagents and conditions used in the examples are conventional methods, reagents and conditions in the art unless otherwise stated.
[0035] An embodiment of the present invention provides a resin composition comprising 100 parts by weight of a vinyl-containing polyphenylene ether resin, 20 to 60 parts by weight of a divinylbenzene-styrene-ethylene terpolymer, and 5 to 15 parts by weight of a compound having a structure of formula (1).
[0036]
[0037] In formula (1), R1, R2, R3, and R4 each independently represent an alkylene group having 1 to 4 carbon atoms or hydrogen.
[0038] In one embodiment, the content of the vinyl-containing polyphenylene ether resin in the resin composition is 100 parts by weight, and the content of other resins or additives is the relative content relative to 100 parts by weight of the vinyl-containing polyphenylene ether resin. For example, unless otherwise specified, the content of the divinylbenzene-styrene-ethylene terpolymer in one embodiment of the present invention is 20 parts by weight to 60 parts by weight relative to 100 parts by weight of the vinyl-containing polyphenylene ether resin. For example, the resin composition in one embodiment of the present invention may include 100 kilograms of the vinyl-containing polyphenylene ether resin and 20 kilograms to 60 kilograms of the divinylbenzene-styrene-ethylene terpolymer. For example, the resin composition in one embodiment of the present invention may include 100 pounds of the vinyl-containing polyphenylene ether resin and 20 pounds to 60 pounds of the divinylbenzene-styrene-ethylene terpolymer.
[0039] In one embodiment, the vinyl-containing polyphenylene ether resin may include various polyphenylene ether resins whose terminals are modified by vinyl, allyl or vinylidene groups. The vinyl-containing polyphenylene ether resin may include vinyl benzyl polyphenylene ether resin, (meth)acrylate polyphenylene ether resin, vinyl benzyl bisphenol A polyphenylene ether resin or maleimide polyphenylene ether resin, but is not limited thereto. The vinyl-containing polyphenylene ether resin having a vinyl, allyl or vinylidene group at the terminal can be polymerized through an unsaturated bond.
[0040] In one embodiment, the vinyl-containing polyphenylene ether resin may include various types of vinyl-containing polyphenylene ether resins known in the art. The vinyl-containing polyphenylene ether resins suitable for the present invention are not particularly limited and may be any one or more commercially available products or homemade products. In certain embodiments, any one or more of the following vinyl-containing polyphenylene ether resins may be used: vinyl-containing benzyl biphenyl polyphenylene ether resin (e.g., OPE-2st, available from Mitsubishi Gas Chemical Co., Ltd.), methacrylate-containing polyphenylene ether resin (e.g., SA9000, available from Sabic Co., Ltd.), or vinyl-containing benzyl bisphenol A polyphenylene ether resin. However, the present invention is not limited thereto.
[0041] In one embodiment, the aforementioned divinylbenzene-styrene-ethylene terpolymer may be a product obtained by polymerization of three monomer units of divinylbenzene, styrene and ethylene obtained by polymerization reaction of three monomer raw materials of divinylbenzene, styrene and ethylene. The aforementioned divinylbenzene-styrene-ethylene terpolymer obtained by polymerization may be a random copolymer, that is, the three monomers of divinylbenzene, styrene and ethylene are cross-linked with each other through a random number arrangement. In another embodiment, the divinylbenzene in the monomer raw material of the divinylbenzene-styrene-ethylene terpolymer may be p-divinylbenzene (p-divinylbenzene).
[0042] In one embodiment, the number average molecular weight (Mn) of the divinylbenzene-styrene-ethylene terpolymer may be between 5,000 and 15,000. In another embodiment, the number average molecular weight of the divinylbenzene-styrene-ethylene terpolymer may be between 5,000 and 11,000. In yet another embodiment, the number average molecular weight of the divinylbenzene-styrene-ethylene terpolymer may be between 6,000 and 10,000.
[0043] In one embodiment, in the polymerization reaction raw materials of the divinylbenzene-styrene-ethylene terpolymer, ethylene may account for about 40 mol% to 80 mol%, styrene may account for about 20 mol% to 60 mol%, divinylbenzene may account for about 0.01 mol% to 10 mol%, and the total amount of divinylbenzene, styrene, and ethylene is 100 mol%. In other embodiments, in the polymerization reaction raw materials of the divinylbenzene-styrene-ethylene terpolymer, ethylene may account for 40 mol% to 80 mol%, styrene may account for 20 mol% to 60 mol%, divinylbenzene may account for 0.01 mol% to 1 mol%, and the total amount of divinylbenzene, styrene, and ethylene is 100 mol%. In other embodiments, in the polymerization reaction raw materials of the divinylbenzene-styrene-ethylene terpolymer, ethylene may account for about 60 mol% to 80 mol%, styrene may account for about 20 mol% to 30 mol%, divinylbenzene may account for about 0.01 mol% to 10 mol%, and the total amount of divinylbenzene, styrene, and ethylene is 100 mol%. In other embodiments, in the polymerization reaction raw materials of the divinylbenzene-styrene-ethylene terpolymer, ethylene may account for 60 mol% to 80 mol%, styrene may account for 20 mol% to 30 mol%, divinylbenzene may account for 0.01 mol% to 1 mol%, and the total amount of divinylbenzene, styrene, and ethylene is 100 mol%. In other embodiments, in the polymerization reaction raw materials of the divinylbenzene-styrene-ethylene terpolymer, ethylene may account for approximately 70 mol% to 80 mol%, styrene may account for approximately 20 mol% to 30 mol%, divinylbenzene may account for approximately 0.01 mol% to 1 mol%, and the total amount of divinylbenzene, styrene and ethylene is 100 mol%.
[0044] In one embodiment, in the compound having the structure of formula (1), R1, R2, R3, and R4 may each independently be a methylene group, an ethylene group, an isobutylene group, or hydrogen. The compound having the structure of formula (1) initiates a polymerization reaction by generating free radicals by breaking the carbon-carbon bonds of two carbon atoms each connected to a benzene ring in the structural formula. For example, the compound having the structure of formula (1) may be a compound having the structure of formula (2), formula (3), or formula (4). For example, the compound having the structure of formula (1) may be 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, or 2,7-dimethyl-4,5-diethyl-4,5-diphenyloctane.
[0045]
[0046] In one embodiment, the resin composition may further include polyolefins other than the divinylbenzene-styrene-ethylene terpolymer, di(vinylphenyl)ethane, maleimide resin, triallylisocyanurate (also known as triallyl isocyanurate), triallyl cyanurate (also known as triallyl cyanurate), styrene maleic anhydride copolymer resin, phenol resin, benzoxazine resin, cyanate resin, polysiloxane resin, polyester resin, epoxy resin, polyamide resin or polyimide resin.
[0047] In one embodiment, the resin composition may further include 1 to 30 parts by weight of a polyolefin other than the divinylbenzene-styrene-ethylene terpolymer relative to 100 parts by weight of the vinyl-containing polyphenylene ether resin, but the present invention is not limited thereto. In another embodiment, when the resin composition includes a polyolefin other than the divinylbenzene-styrene-ethylene terpolymer, the content of the polyolefin may be 1 to 30 parts by weight, or 1 to 15 parts by weight, or 1 to 10 parts by weight. However, the present invention is not limited thereto, and the content of the polyolefin may be adjusted as required. Furthermore, the aforementioned polyolefin other than the divinylbenzene-styrene-ethylene terpolymer may include a vinyl-containing polyolefin or a hydrogenated polyolefin.
[0048] In one embodiment, the resin composition may further include a vinyl-containing polyolefin other than the divinylbenzene-styrene-ethylene terpolymer, and the content of the vinyl polyolefin is not limited. In another embodiment, the resin composition may further include 1 to 30 parts by weight of the vinyl-containing polyphenylene ether resin relative to 100 parts by weight, but the present invention is not limited thereto. In yet another embodiment, the resin composition may not include a vinyl-containing polyolefin other than the divinylbenzene-styrene-ethylene terpolymer, that is, the content of the vinyl-containing polyolefin other than the divinylbenzene-styrene-ethylene terpolymer is 0 parts by weight, which means that the resin composition does not intentionally add a vinyl-containing polyolefin other than the divinylbenzene-styrene-ethylene terpolymer. The types of the aforementioned vinyl-containing polyolefins are not limited, and may include various vinyl-containing olefin polymers known in the art except for divinylbenzene-styrene-ethylene terpolymers, such as but not limited to polybutadiene, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-butadiene-divinylbenzene terpolymer, styrene-butadiene-maleic anhydride terpolymer, vinyl-polybutadiene-urea oligomer or maleic anhydride-butadiene copolymer.
[0049] In one embodiment, the resin composition may further include styrene-butadiene-divinylbenzene terpolymer resin. In another embodiment, the resin composition may not include styrene-butadiene-divinylbenzene terpolymer resin, that is, the content of styrene-butadiene-divinylbenzene terpolymer resin is 0 parts by weight, which means that the resin composition does not specifically add styrene-butadiene-divinylbenzene terpolymer resin.
[0050] In one embodiment, the resin composition may further include hydrogenated polyolefin, and the content of hydrogenated polyolefin is not limited. In another embodiment, relative to 100 parts by weight of vinyl-containing polyphenylene ether resin, the resin composition may further include 1 to 30 parts by weight of hydrogenated polyolefin, but the present invention is not limited thereto. In yet another embodiment, the resin composition may not include hydrogenated polyolefin, that is, the content of hydrogenated polyolefin is 0 parts by weight, and here, it means that the resin composition does not intentionally add hydrogenated polyolefin. The types of the aforementioned hydrogenated polyolefin are not limited, and may include various types of hydrogenated styrene-butadiene-styrene block copolymers (also known as styrene-ethylene / butylene-styrene copolymers) known in the art. The hydrogenated polyolefin suitable for the present invention is not particularly limited and may be any one or more commercially available products or homemade products. For example, the hydrogenated polyolefin may include but is not limited to hydrogenated styrene-butadiene-styrene block copolymers or hydrogenated styrene-butadiene-styrene block copolymers substituted with maleic anhydride. That is, the hydrogenated polyolefin may include, but is not limited to, an unsubstituted hydrogenated styrene-butadiene-styrene triblock copolymer or a hydrogenated styrene-butadiene-styrene triblock copolymer substituted with maleic anhydride. For example, the hydrogenated polyolefin may be: a hydrogenated polyolefin produced by Asahi KASEI with the trade names H1221, H1062, H1521, H1052, H1041, H1053, H1051, H1517, H1043, N504, H1272, M1943, M1911, M1913, etc.; a hydrogenated polyolefin produced by KRATON with the trade names G1650, G1651, G1652, G1654, G1657, G1726, FG1901, FG1924, etc.; or a hydrogenated polyolefin produced by Kuraray with the trade names 8004, 8006, 8007L, etc.
[0051] In one embodiment, the resin composition may further include di(vinylphenyl)ethane, and the content of di(vinylphenyl)ethane is not limited. In another embodiment, relative to 100 parts by weight of the vinyl-containing polyphenylene ether resin, the resin composition may further include 1 to 35 parts by weight of di(vinylphenyl)ethane, but the present invention is not limited thereto. In yet another embodiment, the resin composition may not include di(vinylphenyl)ethane, that is, the content of di(vinylphenyl)ethane is 0 parts by weight, and here, it means that the resin composition does not intentionally add di(vinylphenyl)ethane. In one embodiment, when the resin composition includes di(vinylphenyl)ethane, the content of di(vinylphenyl)ethane may be 1 to 35 parts by weight, or 5 to 35 parts by weight, or 10 to 35 parts by weight. However, the present invention is not limited thereto, and the content of di(vinylphenyl)ethane can be adjusted as required.
[0052] In one embodiment, the resin composition may further include maleimide resin, and the content of maleimide resin is not limited. In another embodiment, relative to 100 parts by weight of vinyl polyphenylene ether resin, the resin composition may further include 1 to 30 parts by weight of maleimide resin, but the present invention is not limited thereto. In another embodiment, the resin composition may not include maleimide resin, that is, the content of maleimide resin is 0 parts by weight, and here, it means that the resin composition does not deliberately add maleimide resin. In another embodiment, when the resin composition includes maleimide resin, the content of maleimide resin may be 1 to 30 parts by weight, or 1 to 20 parts by weight, or 1 to 15 parts by weight, or 5 to 10 parts by weight. However, the present invention is not limited thereto, and the content of maleimide resin can be adjusted as required.
[0053] In one embodiment, the maleimide resin may include 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide (or oligomer of phenylmethane maleimide), bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-dipropyl-4,4'-diphenylmethane bismaleimide, bismaleimide), m-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, N-2,3-dimethylphenylmaleimide, N-2,6-dimethylphenylmaleimide, N-phenylmaleimide, vinyl benzylmaleimide maleimide), maleimide containing biphenyl structure, maleimide resin containing aliphatic long chain structure, prepolymer of diallyl compound and maleimide resin, prepolymer of multifunctional amine and maleimide resin or prepolymer of aminophenol and maleimide resin.
[0054] For example, specific examples of maleimide resins may include, but are not limited to, maleimide resins produced by Daiwakasei Industry with trade names such as BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000, BMI-5000, BMI-5100, BMI-TMH, BMI-7000, and BMI-7000H; maleimide resins produced by KI Chemical Co., Ltd. with trade names such as BMI-70 and BMI-80; or maleimide resins produced by Nippon Kayaku Co., Ltd. with trade names such as MIR-3000 and MIR-5000.
[0055] For example, specific examples of maleimide resins containing aliphatic long chain structures may include, but are not limited to, maleimide resins produced by designer molecular companies under the trade names of BMI-689, BMI-1400, BMI-1500, BMI-1700, BMI-2500, BMI-3000, BMI-5000 and BMI-6000.
[0056] In one embodiment, the resin composition may further include triallyl isocyanurate. In another embodiment, the resin composition may not include triallyl isocyanurate, that is, the content of triallyl isocyanurate is 0 parts by weight, and here, it means that the resin composition does not intentionally add triallyl isocyanurate. In another embodiment, when the resin composition includes triallyl isocyanurate, the content of triallyl isocyanurate may be 1 part by weight to 20 parts by weight, or 1 part by weight to 15 parts by weight, or 1 part by weight to 10 parts by weight. However, the present invention is not limited thereto, and the content of triallyl isocyanurate can be adjusted as needed.
[0057] In one embodiment, in the styrene maleic anhydride copolymer resin (hereinafter referred to as styrene maleic anhydride resin), the ratio of styrene to maleic anhydride may be 1:1, 2:1, 3:1, 4:1, 6:1 or 8:1. Specific examples of the styrene maleic anhydride copolymer resin may include but are not limited to styrene maleic anhydride copolymers sold by Cray Valley under the trade names of SMA-1000, SMA-2000, SMA-3000, EF-30, EF-40, EF-60 and EF-80, or styrene maleic anhydride copolymers sold by Polyscope under the trade names of C400, C500, C700, C900, etc. The styrene maleic anhydride resin may also be an esterified styrene maleic anhydride copolymer, such as the esterified styrene maleic anhydride copolymers available from Cray Valley under the trade names of SMA1440, SMA17352, SMA2625, SMA3840 and SMA31890.
[0058] If not otherwise specified, styrene maleic anhydride resin can be added to the resin composition of one embodiment of the present invention independently or in combination. In one embodiment, when the resin composition includes styrene maleic anhydride resin, the content of styrene maleic anhydride resin can be 1 weight part to 20 weight parts, or 1 weight part to 10 weight parts, or 1 weight part to 5 weight parts. In another embodiment, the resin composition may not include styrene maleic anhydride resin, that is, the content of styrene maleic anhydride resin is 0 weight part. However, the present invention is not limited thereto, and the content of styrene maleic anhydride resin can be adjusted as required.
[0059] In one embodiment, the benzoxazine resin may be a bisphenol A type benzoxazine resin, a bisphenol F type benzoxazine resin, a phenolphthalein type benzoxazine resin, a dicyclopentadiene benzoxazine resin or a phosphorus-containing benzoxazine resin, such as LZ-8270 (phenolphthalein type benzoxazine resin), LZ-8280 (bisphenol F type benzoxazine resin), LZ-8290 (bisphenol A type benzoxazine resin) produced by Huntsman or HFB-2006M produced by Showa Polymer Co., Ltd. In another embodiment, when the resin composition includes the benzoxazine resin, the content of the benzoxazine resin may be 1 part by weight to 10 parts by weight, or 1 part by weight to 5 parts by weight, or 1 part by weight to 3 parts by weight. In yet another embodiment, the resin composition may not include the benzoxazine resin, that is, the content of the benzoxazine resin is 0 parts by weight. However, the present invention is not limited thereto, and the content of the benzoxazine resin may be adjusted as required.
[0060] In one embodiment, the cyanate resin may be any type of cyanate resin known in the art, wherein the cyanate resin may include but is not limited to a cyanate resin having an Ar-OC≡N structure (wherein Ar is an aromatic group, such as benzene, naphthalene or anthracene), a phenol novolac cyanate resin, a bisphenol A cyanate resin, a bisphenol A novolac cyanate resin, a bisphenol F cyanate resin, a bisphenol F novolac cyanate resin, a cyanate resin containing a dicyclopentadiene structure, a cyanate resin containing a naphthalene ring structure or a phenolphthalein cyanate resin. Specific examples of cyanate resins may include but are not limited to cyanate resins produced by Lonza under the trade names of Primaset PT-15, PT-30S, PT-60S, BA-200, BA-230S, BA-3000S, BTP-2500, BTP-6020S, DT-4000, DT-7000, ULL950S, HTL-300, CE-320, LVT-50, LeCy, etc. In another embodiment, when the resin composition includes a cyanate resin, the content of the cyanate resin may be 1 to 10 parts by weight, or 1 to 5 parts by weight, or 1 to 3 parts by weight. In yet another embodiment, the resin composition may not include a cyanate resin, that is, the content of the cyanate resin is 0 parts by weight. However, the present invention is not limited thereto, and the content of the cyanate resin may be adjusted as required.
[0061] In one embodiment, the resin composition may further include a polysiloxane resin (hereinafter referred to as polysiloxane). In another embodiment, the resin composition may not include polysiloxane, and at this time, the content of polysiloxane is 0 parts by weight, and here, it means that the resin composition does not deliberately add polysiloxane. In another embodiment, when the resin composition includes polysiloxane, the content of polysiloxane may be 5 parts by weight to 30 parts by weight, such as 5 parts by weight, 10 parts by weight or 15 parts by weight. However, the present invention is not limited to this, and the content of polysiloxane can be adjusted as needed. The specific example of polysiloxane may include but is not limited to the polysiloxanes produced by Shin-Etsu Corporation under the trade names X-22-161A, X-22-161B, X-22-163A, X-22-163B, X-22-164, etc.
[0062] In one embodiment, the resin composition may further include an inorganic filler, a solvent, a silane coupling agent, a flame retardant, a dye, a toughening agent or a core-shell rubber. The aforementioned components may be used alone or in combination.
[0063] In one embodiment, the resin composition may further include an inorganic filler, and the content of the inorganic filler is not limited. In another embodiment, relative to 100 parts by weight of the vinyl-containing polyphenylene ether resin, the resin composition may further include 30 parts by weight to 130 parts by weight of the inorganic filler, or 50 parts by weight to 130 parts by weight of the inorganic filler, or 65 parts by weight to 125 parts by weight of the inorganic filler. However, the present invention is not limited thereto, and the content of the inorganic filler can be adjusted as required.
[0064] In one embodiment, the inorganic filler may be silica. In one embodiment, the inorganic filler may be spherical silica. Spherical silica may include various types of spherical silica known in the art, and the particle size distribution D50 of the spherical silica may be, for example, less than or equal to 2.0 microns (μm). For example, the particle size distribution D50 may preferably be between 0.2 microns and 2.0 microns, such as but not limited to 0.2 microns, 0.3 microns, 0.4 microns, 0.6 microns, 0.8 microns, 1.2 microns, 1.3 microns, 2.0 microns. If not otherwise specified, the particle size distribution D50 refers to the particle size corresponding to the cumulative volume distribution of the filler (such as but not limited to spherical silica) reaching 50% as measured by laser scattering method. The spherical silica suitable for the present invention is not particularly limited and may be any one or more commercially available products, such as but not limited to spherical silica purchased from Admatechs.
[0065] In one embodiment, the spherical silica can be selectively pre-treated with a siloxane compound as required, and the siloxane compound includes an amino silane compound, an epoxy silane compound, a vinyl silane compound, an ester silane compound, a hydroxy silane compound, an isocyanate silane compound, a methacryloxy silane compound or an acryloxy silane compound. Compared to 100 parts by weight of the spherical silica content, the content of the siloxane compound pre-treatment can be 0.005 parts by weight to 0.5 parts by weight, and is not limited thereto. The amount of the siloxane compound is not particularly limited, and the amount of the siloxane compound added can be adjusted according to the dispersibility of the inorganic filler of the resin composition.
[0066] In one embodiment, the inorganic filler in the resin composition may be an inorganic filler different from spherical silica. The content of the inorganic filler different from spherical silica may be 5 parts by weight to 100 parts by weight, or 10 parts by weight to 80 parts by weight. However, the present invention is not limited thereto, and the content of the inorganic filler different from spherical silica may be adjusted as required.
[0067] In one embodiment, the inorganic filler different from spherical silica includes non-spherical silica (i.e., existing irregular silica, which is not spherical), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, barium titanate, lead titanate, strontium titanate, calcium titanate, magnesium titanate, barium zirconate, lead zirconate, magnesium zirconate, lead zirconate titanate, zinc molybdate, calcium molybdate, magnesium molybdate, ammonium molybdate, zinc molybdate-modified talc, zinc oxide, zirconium oxide, mica, boehmite (AlOOH), calcined talc, talc, silicon nitride or calcined kaolin. In addition, except for the aforementioned non-spherical silica, the remaining aforementioned inorganic fillers may be spherical, fibrous, plate-like, granular, flaky or needle-like. The inorganic filler different from spherical silica may be selectively pre-treated with a siloxane compound as required. The examples and dosage of the siloxane compound used for pre-treating the inorganic filler are as described above and will not be repeated here.
[0068] In one embodiment, the resin composition may further include an inhibitor, and the content of the inhibitor is not limited. In another embodiment, relative to 100 parts by weight of the vinyl polyphenylene ether resin, the resin composition may further include 0.01 parts by weight to 0.5 parts by weight of the inhibitor, but the present invention is not limited thereto. In yet another embodiment, the resin composition may not include an inhibitor, that is, the content of the inhibitor is 0 parts by weight, which means that the resin composition does not intentionally add an inhibitor. In yet another embodiment, when the resin composition includes an inhibitor, the content of the inhibitor may be 0.01 parts by weight to 0.5 parts by weight, for example, 0.02 parts by weight, 0.05 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.45 parts by weight, and 0.5 parts by weight. However, the present invention is not limited thereto, and the content of the inhibitor can be adjusted as needed.
[0069] If not otherwise specified, the inhibitor in the resin composition may be any one or more inhibitors suitable for the production of prepregs, resin films, laminates or printed circuit boards. The inhibitor may include various molecular inhibitors or stable free radical inhibitors known in the art. Molecular inhibitors may include but are not limited to phenolic compounds, quinone compounds, aromatic amine compounds, aromatic nitro compounds, sulfur-containing compounds or variable valence metal chlorides. Specifically, molecular inhibitors may include but are not limited to phenol, hydroquinone, 4-tertiary butylcatechol, benzoquinone, chloranil, l,4-naphthoquinone, trimethylquinone, aniline, nitrobenzene, Na2S, FeCl3 or CuCl2. Stable free radical inhibitors may include but are not limited to 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH), triphenylmethyl radicals, 2,2,6,6-tetramethylpiperidine-1-oxide or derivatives of 2,2,6,6-tetramethylpiperidine-1-oxide.
[0070] In one embodiment, the resin composition may further include a flame retardant. In another embodiment, the resin composition may not include a flame retardant, that is, the content of the flame retardant is 0 parts by weight, and here, it means that the resin composition does not intentionally add a flame retardant. In another embodiment, when the resin composition includes a flame retardant, the content of the flame retardant may be 30 parts by weight to 90 parts by weight, for example, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight or 90 parts by weight. However, the present invention is not limited thereto, and the content of the flame retardant can be adjusted as needed.
[0071] If not otherwise specified, the flame retardant in the resin composition may be any one or more flame retardants suitable for the production of prepregs, resin films, laminates or printed circuit boards, such as but not limited to phosphorus-containing flame retardants. For example, phosphorus-containing flame retardants may include ammonium polyphosphate, hydroquinonebis(diphenyl phosphate), bisphenol A bis(diphenylphosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl)phosphate, trimethyl phosphate (TMP), dimethyl methylphosphonate (DMMP), resorcinol bis(xylyl phosphate) bis(dixylenylphosphate)), RDXP (for example, commercial products such as PX-200, PX-201, and PX-202), phosphazene (for example, commercial products such as SPB-100, SPH-100, and SPV-100), melamine polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives (for example, bis-DOPO compounds) or resins (for example, DOPO-HQ, DOPO-NQ, DOPO-PN, and DOPO-BPN), DOPO-bonded epoxy resins, diphenylphosphine oxide (DPPO) and its derivatives (for example, bis-DPPO compounds) or resins, melamine cyanurate, tri-hydroxyethylisocyanurate, or aluminum phosphinate (for example, products such as OP-930 and OP-935). Among them, DOPO-PN is DOPO phenol novolac resin, and DOPO-BPN can be bisphenol novolac resin such as DOPO-BPAN (DOPO-bisphenol A novolac), DOPO-BPFN (DOPO-bisphenol F novolac) or DOPO-BPSN (DOPO-bisphenol S novolac).
[0072] In one embodiment, the content of the coloring agent, toughening agent or core-shell rubber in the resin composition can be 0.01 to 10 parts by weight, such as but not limited to 0.01 to 3 parts by weight, 0.05 to 1 part by weight. However, the present invention is not limited thereto, and the content of the aforementioned components can be adjusted as required.
[0073] The main function of the solvent is to dissolve the components in the resin composition, change the solid content of the resin composition, and adjust the viscosity of the resin composition. For example, the solvent may include but is not limited to methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, propylene glycol methyl ether, dimethylformamide, dimethylacetamide, nitrogen methyl pyrrolidone or a mixed solvent thereof. The amount of the aforementioned solvent added is not particularly limited, and the amount of the solvent added can be adjusted according to the viscosity required for the resin composition. If a solvent is added to the resin composition, the solvent will be volatilized and removed when the resin composition is heated at high temperature to form a semi-cured state, so there is no solvent in the semi-cured sheet or resin film, or there is only a trace amount of solvent in the semi-cured sheet or resin film.
[0074] If not specifically stated, the coloring agent applicable to the present invention may include but is not limited to dyes or pigments.
[0075] The main function of the toughening agent is to improve the toughness of the resin composition. If not otherwise specified, the toughening agent suitable for the present invention may include but is not limited to carboxyl-terminated butadieneacrylonitrile rubber (CTBN) and other rubbers.
[0076] Unless otherwise specified, the core-shell rubber applicable to the present invention may include various commercially available core-shell rubbers.
[0077] The resin composition of one embodiment of the present invention can be made into various articles through various processing methods, including but not limited to prepregs, resin films, laminates or printed circuit boards.
[0078] For example, the resin composition of one embodiment of the present invention can be made into a prepreg. The prepreg can include a reinforcing material and a layered object disposed on the reinforcing material. The layered object can be obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the prepreg can be between 120°C and 150°C, preferably between 120°C and 130°C, and the baking time can be 3 to 6 minutes. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be various commercially available glass fiber cloths that can be used for printed circuit boards, such as E-type glass fiber cloth, D-type glass fiber cloth, S-type glass fiber cloth, T-type glass fiber cloth, L-type glass fiber cloth or Q-type quartz fiber cloth, wherein the type of fiber can include yarn or roving, and the form can include open fiber or non-open fiber. The non-woven fabric preferably includes a liquid crystal resin non-woven fabric or a quartz non-woven fabric. The liquid crystal resin nonwoven fabric may be, for example, a polyester nonwoven fabric, a polyurethane nonwoven fabric, etc., but is not limited thereto. The fabric may also include a liquid crystal resin fabric, such as a polyester fabric or a polyurethane fabric, etc., but is not limited thereto. The reinforcing material may increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material may also be selectively pretreated with a siloxane compound. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.
[0079] For example, the resin composition of one embodiment of the present invention can be made into a resin film by baking and heating the resin composition to semi-solidify it. The resin composition can be selectively coated on a polyethylene terephthalate film (PET film), a polyimide film (PI film), a copper foil or a copper foil with adhesive backing, and then baked and heated to form a semi-solidified state, so that the resin composition is formed into a resin film.
[0080] For example, the resin composition of one embodiment of the present invention can be made into a laminate. For example, the laminate may include at least two metal foils and at least one insulating layer, and the insulating layer is disposed between the two metal foils. The insulating layer can be formed by pressing and curing the aforementioned resin composition under high temperature and high pressure (C-stage). The applicable curing temperature can be between 220°C and 260°C, preferably between 230°C and 260°C. The curing time can be between 100 and 200 minutes, preferably between 120 and 180 minutes, and the applicable pressure can be between 400 and 600 psi, preferably between 450 and 550 psi. The insulating layer can be obtained by curing at least one semi-cured sheet or at least one resin film. The material of the metal foil can be copper, aluminum, nickel, platinum, silver, gold or their alloys. The metal foil can be, for example, copper foil. In a preferred embodiment, the laminate is a copper clad laminate (also known as a copper clad laminate).
[0081] For example, the metal foil used in the laminate may be a hyper very low profile (HVLP) copper foil or a hyper very low profile 2 (HVLP2) copper foil. The roughness of the matte side of the HVLP copper foil is Rz≤2 (micrometers), and the roughness of the matte side of the HVLP2 copper foil is Rz≤1.5 (micrometers). The definition of roughness Rz is the same as the general definition in the field of copper foil technology, and will not be repeated here.
[0082] For example, in one embodiment, the aforementioned laminate can be further processed into a printed circuit board. The manufacturing method of the printed circuit board can be any existing manufacturing method.
[0083] For example, an article made of the resin composition of one embodiment of the present invention may satisfy one, more or all of the following characteristics:
[0084] The copper foil peel strength of the copper-containing substrate measured by the method described in IPC-TM-650 2.4.8 is greater than 2.90 pounds per inch;
[0085] The water absorption measured by the method described in IPC-TM-650 2.6.2.1a is less than or equal to 0.030%;
[0086] The dielectric loss measured at room temperature and a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 0.00120;
[0087] The article was placed in an environment of 125° C. and heated for 200 hours, then taken out and measured at room temperature and a frequency of 10 GHz according to the method described in JIS C2565, and the dielectric loss was less than or equal to 0.00300.
[0088] The chemical raw materials used in the embodiments and comparative examples of the present invention are as follows:
[0089] SA9000: a polyphenylene ether resin containing methacrylate, commercially available.
[0090] OPE-2st 2200: A vinylbenzyl biphenyl polyphenylene ether resin, commercially available.
[0091] OPE-2st 1200: A vinylbenzyl biphenyl polyphenylene ether resin, commercially available.
[0092] Divinylbenzene-styrene-ethylene terpolymer: a terpolymer of divinylbenzene, styrene and ethylene, wherein ethylene accounts for 70 mol% to 80 mol%, styrene accounts for 20 mol% to 30 mol%, divinylbenzene accounts for 0.01 mol% to 1 mol%, and the total content of divinylbenzene, styrene and ethylene is 100 mol%, and the number average molecular weight of the divinylbenzene-styrene-ethylene terpolymer is between 5,000 and 15,000, and is commercially available.
[0093] Ricon 257: Styrene-butadiene-divinylbenzene terpolymer, commercially available.
[0094] Divinylbenzene-styrene-ethylstyrene terpolymer: as in Synthesis Example 1.
[0095] The compound of formula (2): 2,3-dimethyl-2,3-diphenylbutane is commercially available.
[0096] 25B: 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, commercially available.
[0097] DCP: dicumyl peroxide, commercially available.
[0098] SC2050 SMJ: spherical silica, commercially available.
[0099] B-3000: polybutadiene, commercially available.
[0100] Ricon 100: Styrene-butadiene copolymer, commercially available.
[0101] Ricon 150: polybutadiene, commercially available.
[0102] Ricon 184MA6: styrene-butadiene-maleic anhydride terpolymer, commercially available.
[0103] H1052: hydrogenated styrene-butadiene-styrene block copolymer, commercially available.
[0104] Di(vinylphenyl)ethane: commercially available.
[0105] BMI-3000: maleimide resin of formula (5), commercially available.
[0106]
[0107] Wherein, n is a positive integer from 1 to 10.
[0108] Compound of formula (6): Commercially available.
[0109] Divinylbenzene: commercially available.
[0110] Toluene and butanone: commercially available.
[0111] Synthesis Example 1: Preparation of divinylbenzene-styrene-ethylstyrene terpolymer
[0112] 3.0 mol (390.6 g) of divinylbenzene, 1.8 mol (229.4 g) of ethylvinylbenzene, 10.2 mol (1066.3 g) of styrene and 15.0 mol (1532.0 g) of n-propyl acetate were added to the reactor to obtain a polymerization solution. The polymerization solution was stirred continuously to mix uniformly, and the polymerization solution was heated to 70°C, and 600 mmol of diethyl ether complex of boron trifluoride was added to the polymerization solution, and the polymerization reaction was continued for 4 hours with continuous stirring, and then sodium bicarbonate aqueous solution was added to terminate the polymerization reaction. The oil layer was washed with pure water 3 times, and the volatile components were removed under reduced pressure at 60°C to obtain a divinylbenzene-styrene-ethylstyrene terpolymer.
[0113] The above-mentioned various raw materials were respectively prepared into resin compositions of the embodiments and comparative examples of the present invention according to the amounts shown in Table 1 and Table 4 below, and further prepared into various test samples.
[0114] Table 1: Composition of the resin composition of Examples E1 to E4 (unit: parts by weight)
[0115]
[0116] Table 2: Composition of the resin composition of Examples E5 to E8 (unit: parts by weight)
[0117]
[0118] Table 3: Composition of the resin composition of Comparative Examples C1 to C5 (Unit: parts by weight)
[0119]
[0120] Table 4: Composition of the resin composition of Comparative Examples C6 to C10 (unit: parts by weight)
[0121]
[0122] Gel (or varnish)
[0123] The components of each embodiment (denoted by E, such as E1 to E8) or comparative example (denoted by C, such as C1 to C10) are added into a stirring tank according to the dosage in Tables 1 to 4, and stirred. The resin composition formed after uniform mixing is called resin gel.
[0124] Taking the preparation method of the resin composition of Example E1 as an example, 100 parts by weight of SA9000 and 50 parts by weight of divinylbenzene-styrene-ethylene terpolymer are added to a stirrer containing 120 parts by weight of toluene solvent and 60 parts by weight of butanone solvent, and stirred until SA9000 is completely dissolved and mixed uniformly. Then, 12 parts by weight of the compound of formula (2) is added and stirred until it is completely dissolved and mixed uniformly, and then 100 parts by weight of SC-2050SMJ is added and stirred continuously until it is mixed uniformly to obtain a gel of the resin composition E1.
[0125] In addition, according to the dosage of the ingredients listed in Tables 1 to 4 above, the gels of Examples E2 to E8 and Comparative Examples C1 to C10 were prepared with reference to the gel preparation method of Example E1.
[0126] Referring to the following method, the samples to be tested (prepreg 1, prepreg 2, copper-containing substrate 1, copper-containing substrate 2, copper-free substrate 1 and copper-free substrate 2, respectively) were prepared using the gels of Examples E1 to E8 and Comparative Examples C1 to C10, and then the characteristics were analyzed according to the following specific conditions.
[0127] Prepreg 1 (using 2116E-glass fiber cloth)
[0128] The resin compositions of different embodiments (E1 to E8) and comparative examples (C1 to C10) listed in Tables 1 to 4 were placed in batches in an impregnation tank. Glass fiber cloth (e.g., E-glass fiber fabric with a specification of 2116) was passed through the impregnation tank to attach the resin composition to the glass fiber cloth, and heated at 130° C. for 4 minutes to make it a semi-cured state (B-Stage), thereby obtaining a prepreg 1 (resin content of about 56%).
[0129] Prepreg 2 (using 1035Q-quartz fiber cloth)
[0130] The resin compositions of different embodiments (E1 to E8) and comparative examples (C1 to C10) listed in Tables 1 to 4 were placed in batches in an impregnation tank. A quartz fiber cloth (e.g., Q-quartz fiber cloth with a specification of 1035) was passed through the impregnation tank to attach the resin composition to the quartz fiber cloth, and heated at 130° C. for 4 minutes to make it a semi-cured state (B-Stage), thereby obtaining a prepreg 2 (resin content of about 80%).
[0131] Copper-containing substrate 1 (or copper foil substrate 1, formed by laminating eight prepreg sheets 1)
[0132] Two ultra-low roughness 2 (HVLP2) copper foils with a thickness of 18 μm and eight identical prepregs 1 are prepared, and the copper foil, eight prepregs 1 and copper foil are stacked in this order, and pressed for 150 minutes under vacuum conditions, a pressing pressure of 500 psi, and 235° C. to form a copper-containing substrate 1.
[0133] Copper-containing substrate 2 (or copper foil substrate 2, formed by laminating two prepreg sheets 2)
[0134] Two ultra-low roughness 2 (HVLP2) copper foils with a thickness of 18 microns and two identical prepregs 2 mentioned above are prepared, and the copper foil, two prepregs 2 and copper foil are stacked in the order of laminated, and laminated for 150 minutes under vacuum conditions, a laminating pressure of 500 psi, and 235° C. to form a copper-containing substrate 2.
[0135] Copper-free substrate 1 (made of eight prepreg sheets 1 pressed together)
[0136] The copper foils on both sides of the copper-containing substrate 1 are removed by etching to obtain a copper-free substrate 1 , which is formed by laminating eight identical prepreg sheets 1 .
[0137] Copper-free substrate 2 (made by laminating two prepreg sheets 2)
[0138] The copper foils on both sides of the copper-containing substrate 2 are removed by etching to obtain a copper-free substrate 2, which is formed by laminating two identical semi-cured sheets.
[0139] For the aforementioned samples to be tested, each test method and its characteristic analysis items are described as follows.
[0140] Copper foil peel strength (peel strength, P / S)
[0141] The copper-containing substrate 1 (composed of eight prepreg sheets 1 pressed together) is cut into rectangular test samples with a width of 24 mm and a length greater than 60 mm, and the surface copper foil is etched, leaving only a long strip of copper foil with a width of 3.18 mm and a length greater than 60 mm. The force required to pull the copper foil away from the substrate surface is measured using a universal tensile strength tester at room temperature (about 25° C.) according to the method described in IPC-TM-650 2.4.8 to measure the force (in pounds / inch, lb / in) required to pull the copper foil away from the substrate surface. The higher the copper foil peel strength, the better, and the difference in copper foil peel strength of different test samples is greater than or equal to 0.10 lb / in, indicating that there is a significant difference, indicating that there is a significant technical difficulty. The copper foil peel strength of the copper-containing substrates of Examples (E1 to E8) is greater than 2.90 pounds / inch, for example, greater than 2.93 pounds / inch, and for example, between 2.90 pounds / inch and 3.20 pounds / inch or between 2.93 pounds / inch and 3.14 pounds / inch.
[0142] Dielectric constant (Dk1)
[0143] In the measurement of the dielectric constant, the above-mentioned copper-free substrate 2 (made of two semi-cured sheets 2 pressed together) is selected as the sample to be tested. A microwave dielectrometer (purchased from Japan AET Company) is used, and the method described in JIS C2565 is referred to. Each sample to be tested is measured at room temperature (25°C) and at a frequency of 10GHz to obtain the dielectric constant Dk1 (the dielectric constant Dk1 and the dielectric loss Df1 can be measured simultaneously). The lower the dielectric constant, the better the dielectric properties of the sample to be tested. At a measurement frequency of 10GHz, the difference in Dk1 values of different samples to be tested is less than 0.02, which means that there is no significant difference in the dielectric constant of the substrate, and no significant difference means that there is no significant technical difficulty). The difference in Dk1 values is greater than or equal to 0.02, which means that there is a significant difference between the dielectric constants of different substrates, which means that there is a significant technical difficulty. The dielectric constant Dk1 of the samples to be tested in the embodiments (E1 to E8) is between 2.70 and 2.80. For example, the dielectric constant Dk1 is between 2.71 and 2.78.
[0144] Dielectric constant after heating (Dk2)
[0145] In the measurement of the dielectric constant (Dk2) after heating, the same sample without copper substrate 2 that has been tested for the dielectric constant (Dk1) is selected as the sample to be tested. After placing the sample to be tested in a constant temperature machine and placing it at a constant temperature of 125°C for 200 hours, the sample to be tested is taken out and cooled to room temperature (25°C). Then, a microwave dielectrometer (purchased from Japan AET Company) is used, referring to the method described in JIS C2565, to measure the above-mentioned samples to be tested at room temperature (25°C) and at a frequency of 10GHz to obtain the dielectric constant Dk2 after heating (referred to as dielectric constant Dk2, dielectric constant Dk2 and dielectric loss Df2 can be measured simultaneously). The lower the dielectric constant, the better the dielectric properties of the sample to be tested. At a measurement frequency of 10 GHz, the difference in Dk2 values of different samples to be tested is less than 0.02, which means that there is no significant difference in the dielectric constant of the substrate, which means that there is no significant technical difficulty. The difference in Dk2 values is greater than or equal to 0.02, which means that there is a significant difference between the dielectric constants of different substrates, which means that there is a significant technical difficulty. The dielectric constant Dk2 of the samples to be tested in Examples (E1 to E8) is between 2.70 and 2.80, and for example, the dielectric constant Dk2 is between 2.72 and 2.79.
[0146] Dielectric loss (Df1)
[0147] In the measurement of dielectric loss, the above-mentioned copper-free substrate 2 (made of two semi-cured sheets 2 pressed together) is selected as the sample to be tested. A microwave dielectrometer (purchased from AET, Japan) is used, and the method described in JIS C2565 is referred to. Each sample to be tested is measured at room temperature (25°C) and at a frequency of 10GHz to obtain the dielectric loss Df1 (dielectric constant Dk1 and dielectric loss Df1 can be measured simultaneously). The lower the dielectric loss, the better the dielectric properties of the sample to be tested. At a measurement frequency of 10GHz and in the range of Df1 values of different samples to be tested being less than or equal to 0.00400, the difference in Df1 values less than 0.00010 indicates that there is no significant difference in the dielectric loss of the substrate, and no significant difference indicates that there is no significant technical difficulty. The difference in Df1 values greater than or equal to 0.00010 indicates that there is a significant difference between the dielectric losses of different substrates, indicating that there is a significant technical difficulty. At a measurement frequency of 10 GHz and in a range where the Df1 values of different samples to be tested are greater than 0.00400, a difference in Df1 values less than 0.00050 indicates that there is no significant difference in the dielectric loss of the substrates, and a difference in Df1 values greater than or equal to 0.00050 indicates that there is a significant difference in the dielectric loss of different substrates. The dielectric loss Df1 of the samples to be tested in Examples (E1 to E8) measured at room temperature and a frequency of 10 GHz is between 0.00100 and 0.00120, and for another example, the dielectric loss Df1 is between 0.00101 and 0.00112, and the dielectric loss Df1 is less than or equal to 0.00120.
[0148] Dielectric loss after heating (Df2)
[0149] In the measurement of the dielectric loss (Df2) after heating, the same sample without the copper substrate 2 that was tested for the dielectric loss (Df1) was selected as the sample to be tested. The sample to be tested was placed in a constant temperature machine and placed at a constant temperature of 125°C for 200 hours. The sample to be tested was taken out and cooled to room temperature (25°C). Then, a microwave dielectrometer (purchased from Japan AET Company) was used to measure the above-mentioned samples at room temperature (25°C) and at a frequency of 10GHz with reference to the method described in JIS C2565 to obtain the dielectric loss Df2 after heating (referred to as dielectric loss Df2, the dielectric constant Dk2 and dielectric loss Df2 can be measured simultaneously). The lower the dielectric loss, the better the dielectric properties of the sample to be tested. At a measurement frequency of 10 GHz and in a range where the Df2 value is less than 0.00400, a difference in the Df2 value of less than 0.00010 indicates that there is no significant difference in the dielectric loss of the substrates, and no significant difference indicates that there is no significant technical difficulty. A difference in the Df1 value of greater than or equal to 0.00010 indicates that there is a significant difference in the dielectric loss of different substrates, indicating that there is a significant technical difficulty. At a measurement frequency of 10 GHz and in a range where the Df2 value is greater than 0.00400, a difference in the Df1 value of less than 0.00050 indicates that there is no significant difference in the dielectric loss of the substrates, and a difference in the Df2 value of greater than or equal to 0.00050 indicates that there is a significant difference in the dielectric loss of different substrates. The dielectric loss Df2 of the samples to be tested in Examples (E1 to E8) is between 0.00220 and 0.00280 when measured at room temperature and a frequency of 10 GHz after being heated. For example, the dielectric loss Df2 is between 0.00225 and 0.00273, and the dielectric loss Df2 is less than or equal to 0.00300.
[0150] Bending strength
[0151] In the bending strength test, a copper-free substrate 2 (made of eight prepregs pressed together) with a length of 3 inches (the length direction refers to the warp direction of the glass fiber cloth) and a width of 1 inch (the width direction refers to the weft direction of the glass fiber cloth) for each sample to be tested is selected. Three samples to be tested are tested in each set of embodiments and comparative examples, and the average bending strength of the three samples to be tested is recorded. First, the actual width and thickness (both in mm) of each sample to be tested are measured and input into a computer connected to a universal testing machine, and then the samples are placed on the loading platform respectively, and the test is started with a universal testing machine (brand Shimadzu, model AG-5KNX Plus) and a special fixture for anti-bending experiment (brand Shimadzu, model SLBL-5KN). When the universal testing machine determines that the test sample is broken, the universal testing machine will calculate the maximum load (unit N) when the sample breaks and the distance (unit mm) traveled by the fixture when the sample breaks. The computer connected to the universal testing machine will calculate the flexural strength according to the built-in span of the machine (fixed at 20 mm) and the above maximum load and travel distance. The calculation formula is: Flexural Strength = [(3×maximum load×span)÷(2×sample width×square of sample thickness)]. The flexural strength of the samples to be tested in Examples (E1 to E8) is 45,000 pounds / (inch) 2 The above, and wherein the bending strength of the samples to be tested in Examples E1, E2, E5, E7, and E8 is 50,000 pounds / (inch) 2 above.
[0152] Classification of flexural strength test results:
[0153] Grade A: Flexural strength greater than or equal to 50,000 (lbs / (in)) 2 ), such as flexural strength between 50,000 and 55,000 (lbs / (in) 2 )between
[0154] Grade B: Flexural strength between 45,000 and 49,999 (lbs / (in)) 2 )between
[0155] Grade C: Flexural strength between 40,000 and 44,999 (lbs / (in)) 2 )between
[0156] Grade D: Flexural strength less than or equal to 39,999 (lbs / (in)) 2 )
[0157] Appearance without copper substrate
[0158] The surface condition of the insulating layer of the copper-free substrate 1 (composed of eight prepregs 1 pressed together) is determined by visual observation. The surface insulating layer of the copper-free substrate is visually observed to see if there are dry plates or dendritic stripes. The distribution of dry plates is shown in the schematic diagram. Figure 1 The dry plate represents the surface of the insulating layer without copper substrate 1, and the texture is exposed (or the insulating layer surface lacks glue). The schematic diagram of the surface insulating layer without copper substrate has no dry plate and no dendritic stripes as shown in FIG. Figure 2 and Figure 4 The dendritic stripe distribution on the edge of the board without copper substrate surface insulation layer indicates that the compatibility of the resin composition is poor or the fluidity difference is large, resulting in unevenness. The schematic diagram of the dendritic stripe distribution is shown in Figure 3 As shown, the more dendritic stripes there are, the more serious the dendritic phenomenon is. If there is at least one stripe greater than or equal to 1 mm, it is recorded as the presence of board edge dendritic stripes. The presence of dry plates or dendritic distribution areas on the surface insulation layer of the copper-free substrate will cause the subsequent circuit board to have uneven characteristics (poor reliability) and a significant reduction in yield, such as poor dielectric properties, low heat resistance, uneven thermal expansion, or poor interlayer adhesion. The circuit board with the above-mentioned defects will need to be directly scrapped. The appearance of the copper-free substrates of Examples (E1 to E8) does not have dry plates and dendritic stripes.
[0159] Water absorption rate
[0160] In the water absorption test, a copper-free substrate 1 (made of eight prepreg sheets 1 pressed together) with a length of 2 inches and a width of 2 inches is selected as the sample to be tested. Each sample to be tested is placed in an oven at 105±10°C for baking for 1 hour and then taken out. After cooling at room temperature (about 23°C) for 10 minutes, the weight of the copper-free substrate 2 is weighed as W1. Next, the copper-free substrate 2 after weighing is placed in pure water at room temperature and soaked for 24 hours and then taken out. The water remaining on the surface of the substrate is wiped off. The weight after wiping off is weighed as the weight of the copper-free substrate 2 after water absorption, which is W2. According to the formula: water absorption W (%) = [(W2-W1) / W1] × 100%, the water absorption is calculated, and the water absorption of each sample to be tested is measured with reference to the method described in IPC-TM-650 2.6.2.1a, and the unit is %.
[0161] In the art, the lower the water absorption, the better. When the difference in water absorption between different samples is greater than or equal to 0.010%, it means that there is a significant difference in water absorption between different substrates, indicating that there is a significant technical difficulty. For example, the water absorption of an article made of a resin composition according to an embodiment of the present invention is less than or equal to 0.030% measured by the method described in IPC-TM-6502.6.2.1a, for example, between 0.020% and 0.030%.
[0162] Glass transition temperature
[0163] In the glass transition temperature test, the above-mentioned copper-free substrate 1 (made of eight semi-cured sheets 1 pressed together) is selected as the sample to be tested. Using dynamic mechanical analysis (DMA), the glass transition temperature (in °C) of the sample to be tested is measured with reference to the method described in IPC-TM-6502.4.24.4. The measurement temperature range is 35°C to 270°C, and the temperature rise rate is 2°C / minute. The higher the glass transition temperature, the better the properties. Measured by dynamic mechanical analysis, the glass transition temperature of the samples to be tested in Examples (E1 to E8) is greater than or equal to 180°C, indicating that the copper-free substrate 1 has reached the basic heat resistance properties of the laminate.
[0164] According to the above embodiments, articles made of the resin composition of the present invention, such as prepregs, resin films, laminates or printed circuit boards, have excellent properties in at least one of the copper foil peel strength, water absorption, dielectric loss, bending strength and glass transition temperature of copper-containing substrates, and can thus become high-performance substrates that meet comprehensive requirements.
Claims
1. A resin composition, characterized in that Include: 100 parts by weight of a vinyl-containing polyphenylene ether resin; 20 to 60 parts by weight of a divinylbenzene-styrene-ethylene terpolymer; and 5 to 15 parts by weight of a compound having the structure of formula (1), Wherein, R1, R2, R3, and R4 each independently represent an alkylene group having 1 to 4 carbon atoms or hydrogen.
2. The resin composition according to claim 1, wherein R1, R2, R3, and R4 are each independently methylene, ethylene, isobutylene or hydrogen.
3. The resin composition according to claim 1, wherein the compound having the structure of formula (1) is a compound having the structure of formula (2), formula (3) or formula (4), 4. The resin composition according to claim 1, wherein the vinyl-containing polyphenylene ether resin comprises a vinyl benzyl-containing polyphenylene ether resin, a (meth)acrylate-containing polyphenylene ether resin, a vinyl benzyl bisphenol A-containing polyphenylene ether resin or a maleimide-containing polyphenylene ether resin.
5. The resin composition according to claim 1, wherein the number average molecular weight (Mn) of the divinylbenzene-styrene-ethylene terpolymer is between 5,000 and 15,000.
6. The resin composition according to claim 1, wherein the divinylbenzene-styrene-ethylene terpolymer is prepared by polymerization of 40 mol % to 80 mol % of ethylene monomer, 20 mol % to 60 mol % of styrene monomer and 0.01 mol % to 10 mol % of divinylbenzene monomer, and the total amount of the divinylbenzene monomer, the styrene monomer and the ethylene monomer is 100 mol %.
7. The resin composition according to claim 1, wherein It also includes polyolefins other than divinylbenzene-styrene-ethylene terpolymers, di(vinylphenyl)ethane, maleimide resins, triallyl isocyanurate, triallyl cyanurate, styrene maleic anhydride copolymer resins, phenol resins, benzoxazine resins, cyanate resins, polysiloxane resins, polyester resins, epoxy resins, polyamide resins or polyimide resins.
8. The resin composition according to claim 1, wherein Also contains inorganic fillers.
9. An article made of the resin composition according to any one of claims 1 to 8, wherein The article comprises a prepreg, a resin film, a laminate or a printed circuit board.
10. The article according to claim 9, wherein This item has at least one of the following properties: The copper foil peel strength of the copper-containing substrate measured by the method described in IPC-TM-650 2.4.8 is greater than 2.90 pounds per inch; The water absorption measured by the method described in IPC-TM-650 2.6.2.1a is less than or equal to 0.030%; The dielectric loss measured at room temperature and a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 0.00120; The article was placed in an environment of 125° C. and heated for 200 hours, then taken out and measured at room temperature and a frequency of 10 GHz according to the method described in JIS C2565, and the dielectric loss was less than or equal to 0.00300.